2013
DOI: 10.1590/s0365-05962013000200024
|View full text |Cite
|
Sign up to set email alerts
|

Lobomycosis and squamous cell carcinoma

Abstract: The occurence of squamous cell carcinoma on long-lasting ulcers is classic. Malignant transformation may occur on burn scars and chronic ulcers of varying etiology, including infectious agents. Transformation of old lobomycosis lesion scars into squamous cell carcinoma has been rarely reported. Careful and long-term follow-up of such patients is important to avoid carcinomatous transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 4 publications
0
10
0
1
Order By: Relevance
“…In another study reported by Nogueira et al [ 32 ], a 87-year-old man presented a 30-year history of disseminated cutaneous lesions. He also noted that a lesion on the lower right limb had ulcerated during the prior seven months.…”
Section: Discussionmentioning
confidence: 98%
“…In another study reported by Nogueira et al [ 32 ], a 87-year-old man presented a 30-year history of disseminated cutaneous lesions. He also noted that a lesion on the lower right limb had ulcerated during the prior seven months.…”
Section: Discussionmentioning
confidence: 98%
“…Long-term complications of lobomycosis infection can lead to squamous cell carcinoma (Beltrame et al, 2017;Grayson & Colonje, 2020). Nogueira, 2013 reported a case of squamous cell carcinoma associated with lobomycosis based on clinical findings and histopathological features (Nogueira et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Cutaneous leishmaniasis is the most common condition in the differential diagnosis for lobomycosis, especially if the lobomycosis is ulcerated, which is a frequent complication. Four case-patients with lobomycosis, 1 of whom died, were reported to have squamous cell carcinomas ( 3 , 44 ). However, the acrolentiginous melanoma that resulted in the death of case-patient 2 in our report was not related to lobomycosis.…”
Section: Discussionmentioning
confidence: 99%